INTED2019 Proceedings 2019
DOI: 10.21125/inted.2019.2112
|View full text |Cite
|
Sign up to set email alerts
|

Strengths, Weaknesses, Opportunities and Threats for Using Reusable Learning Objects in European Healthcare Curricula to Enhance Cultural Sensitivity

Abstract: Health care is becoming increasingly culturally diverse and there is a growing need for nurses to deliver culturally competent care patient centred care. Therefore, it is imperative that nurses are equipped with an awareness of what it means to possess cultural sensitivity. Internationally competent nurses need an awareness of cultural issues that challenge their attitudes and beliefs to reflect multicultural professionalism. Culturally competent professionals play a critical role in reducing health disparitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Partners identified strengths and challenges within the application of ASPIRE framework into the development process. Partners that were not familiar with the process required further training apart from the initial train the trainers' workshop, while all partners identified further potential opportunities of applying the process to develop modern curricula encompassing new teaching methods, which is in agreement with previous findings from Brown et al [19].…”
Section: Discussionsupporting
confidence: 82%
“…Partners identified strengths and challenges within the application of ASPIRE framework into the development process. Partners that were not familiar with the process required further training apart from the initial train the trainers' workshop, while all partners identified further potential opportunities of applying the process to develop modern curricula encompassing new teaching methods, which is in agreement with previous findings from Brown et al [19].…”
Section: Discussionsupporting
confidence: 82%
“…TransCoCon is an Erasmus+ strategic partnership in Higher Education of five European higher education institutions from UK, Germany, Portugal, Ireland and Belgium. It focuses on enhancing cultural awareness and promotion of transcultural competence in nursing as it has been suggested that health disparities exist within in ethnic minorities and by providing culturally competent care could reduce disparities [10].…”
Section: The Transcocon Erasmus+ Projectmentioning
confidence: 99%
“…Integrated E-Learning Objects Design Model and Implementation into Educational Platforms help reduce the time developing instructions and help share knowledge between universities [8]. The weakness of reusable learning instructions is that they could be outdated [9]. Platforms could be underusage as enterprises won't use educational organisation platforms and sheer them between enterprises.…”
Section: Literature Reviewmentioning
confidence: 99%